Existence Results for a Class of the Quasilinear Elliptic Equations with the Logarithmic Nonlinearity. (19th December 2020) - Cui, Zhoujin; Mao, Zisen; Zong, Wen; Zhang, Xiaorong; Yang, Zuodong
Abstract : In this paper, the nonlinear quasilinear elliptic problem with the logarithmic nonlinearity − div ∇ u p − 2 ∇ u = a x φ p u log u + h x ψ p u in Ω ⊂ R n was studied. By means of a double perturbation argument and Nehari manifold, the authors obtain the existence results.